Kepuasan Mahasiswa Teknologi Informasi Terhadap Kualitas Pelayanan Laboratorium Komputer Institut Shanti Bhuana - Kusnanto; Azriel Christian Nurcahyo; Listra Firgia (Infact: International Journal of Computers, 2023)
In the implementation of learning activities, it is necessary to support good facilities and infrastructure so that they can run smoothly. One of the learning facilities needed is a computer laboratory. Shanti Bhuana's IT Study Program has supporting facilities in improving the teaching and learning service process, one of the facilities provided is a computer laboratory. As a form of measuring the role of the computer laboratory on student satisfaction in developing the learning process, it is necessary to measure the quality of service so that it can support the role and function of the laboratory optimally. In this study, it is explained how the quality of computer laboratory services in improving teaching and learning skills based on criteria that become benchmarks are tangibles, reliability, responsiveness, empathy, assurance, courtesy, credibility, secure, and communication. Data analysis using descriptive statistical calculations. From the results of the research analysis, it was concluded that the overall computer laboratory service was still relatively good, it could be seen from the average of 5 service quality measurement indicators consisting of 14 questions getting an average score of 178.64 indicating that the computer laboratory service was in the fairly good category. From this research, there are still many things that need to be improved, and researchers provide suggestions, such as adding computer tools or equipment and internet access power by optimizing the functions of the facilities and infrastructure that are already available.